Una relazione per un'accademia (Balthazar, 2024)
My writing focuses on one of Kafka’s most stimulating stories: Ein Bericht für eine Akademie, from 1922. It traces the path of an animal (the monkey Peter the Red) who, once captured, is forced to find an escape route by becoming man. However, it is not certain that the transition to human life is a gain for him, nor that the animal dimension is preferable. The message that Kafka leaves us is that it is important to remember, not to forget what you think you have emancipated from (from your past, from your animal dimension), and not to forget that you have forgotten; because in an oblivion that knows how to recognize and denounce itself there is a possible hope. It’s about not forgetting the worst that happened, of course. But oblivion is not only oblivion of the worst, but also “of the best”. In the forgotten, removed animal dimension, there is not only the worst of the bestiality from which we have freed ourselves, but also the best of a possibility of redemption, in a credible freedom.